Effects of Non-Surgical Periodontal Therapy on Glycemic Control in Prediabetes and Diabetes Patients with Stage II–IV Periodontitis as Monitored by Active-Matrix Metalloproteinase-8 Levels - Kehinde Adesola Umeizudike; Solomon Olusegun Nwhator; Olayiwola Ibrahim Olaoye; Ayodele Charles Ogundana; Ismo T. Räisänen; Olufemi Adetola Fasanmade; Oladunni Ogundana; Obiefuna Ajie; Timo Sorsa (Biomedicines)
Background/Objectives: Previous research indicates that non-surgical periodontal therapy (NSPT) improves glycemic control in individuals with prediabetes and diabetes who have periodontitis. Few studies have demonstrated its effects on mouthrinse active-matrix metalloproteinase-8 (aMMP-8) levels as it relates to glycemic control. We assessed the periodontal treatment response of stage II–IV periodontitis patients with prediabetes, diabetes, and normoglycemia, regarding glycated hemoglobin (HbA1c) and mouthrinse aMMP-8 levels using point-of-care kits (PoC). Materials and Methods: Eighty-eight adults (11 normoglycemic, 32 prediabetic, 45 with type 2 diabetes), aged 25–78, with stage II–IV periodontitis were included. Full-mouth clinical examinations were used to evaluate their periodontal parameters. HbA1c and mouthrinse aMMP-8 levels were assessed using PoC kits before and approximately three months after scaling and root planing. Results: There were positive treatment effects of non-surgical periodontal therapy on periodontal clinical parameters, aMMP-8 and HbA1c levels in the prediabetes and diabetes groups. The aMMP-8 reduction was significant (p < 0.001) in the prediabetes and prediabetes + diabetes groups, while HbA1c decreased significantly in the diabetes and prediabetes + diabetes (p < 0.001) groups. In contrast, a non-significant increase in mean aMMP-8 levels, HbA1c, and CAL was observed in normoglycemia (p > 0.05). Stage III + IV periodontitis showed significant treatment effects for aMMP-8 (p < 0.001) and HbA1c (p < 0.01) compared to stage II, regardless of glycemic status. Conclusions: Non-surgical periodontal therapy significantly improves periodontal health as well as HbA1c and aMMP-8 levels in people living with prediabetes and diabetes.